Aggression and antisocial behavior in individuals with mobile phone dependence: A possible factor conducive to crime - Olmedo Hernández, Isaac Jahir (2019)
Objective: To determine the frequency of aggression and antisocial behavior in university students with mobile phone dependence. Materials and methods: Sixty-six (66) university students from 18 to 25 years old (54.5 % females) participated in the study. They completed the Mobile Phone Problematic Use Scale (MPPUS) to assess the mobile phone dependence, and the Minnesota Multiphasic Personality Inventory 2-RF (MMPI-2-RF) to assess the antisocial behavior and aggression. Results: Twenty-two point seven percent (22.7 %) of the sample showed mobile phone dependence (cutoff point: 80th percentile). Additionally, a statistical significance (p <0.01) was observed in eight scales of the MPPI-2-RF, including CR4, AG and AGGR-r, which are related to aggression and antisocial behavior. Conclusions: There is a relationship between mobile phone dependence and the scales assessing aggression and antisocial behavior. We postulate that mobile phone dependence could be a factor conducive to crime.